Pelatihan Administrasi Perkantoran Masa Pandemi di Kelurahan Gading Cempaka - Ditasman, Ditasman; Siregar, Syahril Hasan; Jumiati, Monica; Ristiayunita, Eriska; Saputra, Aditya Rahmat (Jurnal Kewirausahaan dan Bisnis, 2021)
The 21st century, Industrial Revolution 4.0, Covid-19 pandemic, accelerates organizational transformation by optimizing online media and methods as organizational needs. The Covid pandemic has been running for more than a year, but office administration staff and the secretary of the institutional assembly, as human resources responsible for preparing online media, still often face technical problems that cannot be resolved quickly. The goal to be achieved in this service program is to provide education and training so that staff and secretaries of institutions can optimize online media and methods and can solve technical problems in emergencies. The method of implementation of this program is online training to provide a basic general understanding, followed by offline training to practice zoom webinar media, as MC and Online Moderator. The results and implications of this program are being able to understand and implement online media such as zoom, and others.